Hand Washing Training for Posyandu Cadres - Ida Susila; Asyaul Wasiah; Siti Sholikha; Eylen Krisna Sari (Journal of Community Engagement in Health, 2025)
Washing Hands with Soap (CTPS) is a form of Clean and Healthy Living Behavior (PHBS) to prevent and control diarrhea and typhoid infections, especially in children. The incidence of diarrhea and typhoid infections in children is still high. Hand hygiene is one factor in preventing the transmission of diarrhea and typhoid infections through food handled with dirty hands. The healthy behavior of washing hands with soap, which is one of the Clean and Healthy Living Behaviors (PHBS), has now become a global concern, this is because the problem of lack of practice of hand washing behavior does not only occur in developing countries, but also in other countries. Therefore, hand washing training is needed for posyandu cadres as an intermediary for achieving PHBS through washing hands with soap.